Numerical Analysis and Taguchi Optimization of Bird Strike Resistance on Helicopter Engine Cowling Using Lattice Structure - Budi Aji Warsiyanto; Muhammad Hadi Widanto; Rafika Arum Sari; Alfan Rizki; Rizky Akmal Putera (Green Publisher Indonesia, 2025)
Bird strikes pose a major risk to the safe operation of aircraft. This study evaluates a sandwich structure design with a lattice material as a helicopter engine protection device. Advances in additive manufacturing have enabled the advancement and fabrication of architected cellular materials. The lattice structures were assessed computationally through nonlinear dynamic finite element method, considering variations in topology, materials, and relative density. The Taguchi approach was used to establish the ideal lattice structure by maximizing specific energy absorption (SEA). The results showed that a body-centered cubic Z (BCCZ) lattice structure using Ti-6Al-4V material and 30% relative density performed the best at absorbing impact energy. Additionally, the sandwich structure that uses BCCZ lattice, effectively protected the engine cowling under the operational speed of a helicopter. The findings indicate that the BCCZ lattice core enhances the impact resistance of composite materials by minimizing structural deformation. Moreover, a quasi-isotropic layup combined with a lattice material sandwich plate provides superior impact resistance, deformation control, and damage mitigation compared to other sandwich designs.